Experimental Models Point Mutations In Plasmodium falciparum pfatpase6 Gene Exposed to Recuring Artemisinin In Vitro - Maslachah, Lilik; Dachlan, Yoes Prijatna; Nidom, Chairul A.; Fitr, Loeki Enggar (KnE Life Sciences, 2017)
The aims of this research to prove that repeated exposure of artemisinin can cause pfatpase6 gene mutation on Plasmodium falciparum in vitro. The research methods used culture In Vitro Plasmodium falciparum of strain 2300 IC50 value determination test artemisinin, artemisinin repeated exposure test (PO1, PO2, PO3 dan PO4) dose IC50, DNA extraction, gene amplification of pfatpase6 using Polymerase Chain Reaction (PCR) technique, electrophoresis, PCR product purification, labeling DNA from PCR results, DNA precipitation of PCR product, application of product labeling on the sequencing machines, analysis of the results of sequencing, and Data Analysis. The results of PCR pfatpase6 gene amplification include region 6 – 3216 for codon 89-1031 located in exon 1 and 2 Plasmodium falciparum 2300 by using five pairs of primers. Primer pair 1FR produce a long amplicon of 737 bp which covers of codon 89; primer pair 2FR produce a long amplicon of 813 bp which covers of codon 263, 431; primer pair 4FR produce a long amplicon of 700 bp which covers of codon 460, 465, 623; primer pair 5FR produce a long amplicon of 550 bp which includes of codon 683, 769; and primer pair 6FR produce a long amplicon of 876 bp which covers of codon 898, 1031.Multialigment pfatpase6 gene Plasmodium falciparum of strains Papua 2300 point mutations are obtained in the form of transition and transversion in treatment groups at the same nucleotide region 123, 2035, 2043, 2138 dan 2148. Conclusion of this research Artemisinin repeated exposure can cause point mutations in pfatpase6 genes Plasmodium falciparum of strains 2300 in vitro Keyword: Artemisinin, Plasmodium falciparumof strain Papua 2300, pfatpase6 gene, point mutation